DARI TRADISIONAL MENUJU DIGITAL: ADOPSI INTERNET OLEH NAHDLATUL ULAMA SELAMA PANDEMI COVID-19 - Muhammad Irfan Wahid (Jurnal Studi Agama dan Masyarakat, 2020)
This article discussed on how religious organizations see and use the internet. The example of a case presented in this article was a mass organization of Nahdlatul Ulama. This article was based on assumption that Nahdlatul Ulama as a traditionalist religious organization tends to be conservative towards the development of information technology was an inaccurate analysis. The data in this article were obtained from Nahdlatul Ulama official website and literature. The findings indicated that despite having a traditionalist character, Nahdlatul Ulama was able to adopt internet technology as an information media for its religious worldviews.